The Humanized Health Care Model for Nursing Care Pregnancy Women: Knowledge from Nursing Student Experiences - Sosome, Boonsurb; Wiwekwan, Yodsoy; Suwannaka, Yoavadee (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This qualitative research aimed to study the model of humanized health care for pregnancy women of nursing students, from Boromarajonani College of Nursing, Praputhabat. Data collected from 68 of the 2nd nursing students of Bachelor Nursing Program practicing in the Maternal, Newborn and Midwifery Nursing Care Course. Field notes, participation observations were used gathering data during nursing students practiced in the antenatal care department and during conference in clinical practice, as well as focus group after finished course. Guideline Question of the Experiences of Humanized Health Care of Nursing Students was used to focus group discussion. Data analyzed by content analysis. Confirm validities themes emerged together with participants. Findings demonstrated the model was including (1) Constructed relationships by ask for permission before assess history of pregnancy and physical examination. Trust was made by greet, smile, and well speak perform concerning. (2) Provided human right, and equality. (3) Respectively belief and culture. (4) Conducted family centered-care, spouse support helping the decision making. (5) Supported the unwanted pregnancy to decrease anxiety. Outcomes of practicing were consisted of (1) easily to work and got really data from pregnancy women (2) deeper understanding and happy to practice.